Performance evaluation of scenerio-aware protocol for producer mobility support in NDN - Ahmed, Muhammed Zaharadeen; Hassan Abdalla Hashim, Aisha; Hassan, Afaf Mirghani; Khalifa, Othman Omran; Mohd Ramli, Huda Adibah; Alkali, Abdulkadir Hamidu (IEEE, 2019)
A scenario-aware is a type of protocol designed to enable NDN applications have specific interest/data naming convention and specific message exchange. Location update and Handoff analysis are the two basic classes of managing network mobility in both IP and NDN. Location update focus mainly on updating producer’s mobility/movement information while handoff focus mainly on ensuring network access as the mobile producer continues to relocate/change its (Point of Attachment) PoA to another. Thus, the frequent mobility of the NDN producer is one high significant features of network mobility in an NDN environment. In this paper, the mobile producer is anchorless and is required to frequently change its Care of Address (CoA) as it relocates between multiple NDN access networks. This then has absolute effect on network performance of the mobility management at mobile producer’s handoff. Therefore, a performance analysis for the mobile producer handoff between different NDN access networks using NDN scenario-aware protocol is presented using analytical approach and to be supported with simulation. Simulations were carried out using ndnSim 2.1 NS3-based. Analysis were estimated for delay during handoff and packet loss for interest/data exchange between mobile producers.